An Cháilíocht sa Ghaeilge agus an Fráma Tagartha Comónta Eorpach do Theangacha. - Whelton, Marie; Mac Suibhne, Aodán; Mac Giolla Bhríghde, Peadar (Irish National Teachers' Organisation, 2017)
An overview of the Irish Language Requirement Syllabus and the CEFRL.
Keywords: The Common European Framework of Reference for Languages; CEFR; An Cháilíocht sa Ghaeilge (SCG); Irish Language Requirement; Irish language; Gaeilge; CEFRL; Teacher education; Education--Ireland; Irish language--Study and teaching